Core biopsies of the breast: Diagnostic pitfalls - Megha Joshi; Sriharshan J Reddy; Manjiri Nanavidekar; John P Russo; Armand V Russo; Ram Pathak (Wolters Kluwer Medknow Publications, 2011)
The incidence of breast cancer is increasing worldwide. In this review article, the authors compare and contrast the incidence of breast cancer, and the inherent differences in the United States (US) and India in screening techniques used for diagnosing breast cancer. In spite of these differences, core biopsies of the breast are common for diagnosis of breast cancer in both countries. The authors describe "Best Practices" in the reporting and processing of core biopsies and in the analysis of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor Receptor 2 (Her2/neu). The pitfalls in the diagnosis of fibroepithelial lesions of the breast on core biopsy are discussed, as also the significance of pseudoangiomatous stromal hyperplasia of the breast (PASH) is discussed in core biopsy. In this review, the management and diagnosis of flat epithelial atypia and radiation atypia are elaborated and the use of immunohistochemistry (IHC) in papillary lesions, phyllodes tumor, and complex sclerosing lesions (radial scars) is illustrated. Rarer lesions such as mucinous and histiocytoid carcinoma are also discussed.